QnA-based Learning Platform Using Instant Messaging and Deep Learning - Hadi Suprayitno; Wan Sen Tjong (LPPM, 2025)
The explosion of instant messaging apps has created a new paradigm for learning and knowledge sharing. In this paper, we introduce an innovative Q&A-based learning platform that leverages the power of instant messaging and deep learning to provide inexpensive personalized learning experiences for students. This helps those who may not have access to teachers or need more support outside of regular class hours. Our platform utilizes deep learning technology and/or natural language processing to analyze and respond to students' queries in almost real-time and nonstop 24/7. By integrating instant messaging with deep learning, this platform enables students to engage in interactive and conversational learning experiences. Personal or private messages enable learning systems that are tailored to individual needs and learning styles. We used the Rapid Application Development method with an object-oriented approach to create this platform. We demonstrate the proof of concept of this platform through a series of experiments and evaluations. Based on the results of the trial, the designed platform can attract the attention of many students when learning. The contributions of this paper are threefold. First, we propose a novel Q&A-based learning platform that integrates instant messaging and deep learning to provide personalized learning experiences. Second, we demonstrate the effectiveness of our platform through a series of experiments and evaluations. Finally, we provide a framework for future research and development in the area of intelligent Q&A platforms for personalized learning.